IMPLEMENTASI SIKAP KARAKTER DISIPLIN BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN KARAWACI BARU 6 KOTA TANGERANG - Intan Safitri; Erdhita Oktrifianty; M. Imam Muttaqijn (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the persistence of learning discipline issues among fourth-grade students in Pancasila Education, including non-compliance with school regulations, late assignment submission, failure to bring learning materials, and inconsistent learning habits. These settings highlight the importance of improving pupils' study discipline as part of character education. The study sought to characterize the application of the learning discipline character in Pancasila Education, identify the obstacles faced by teachers, and examine the techniques used to overcome those challenges. The qualitative descriptive approach was used in this study. Participants included a fourth-grade teacher, fourth-grade pupils, and parents from SDN Karawaci Baru 6, Tangerang City. Data were gathered by observation, interviews, and documentation, and then analyzed using the Miles and Huberman interactive model, which included data reduction, data display, and conclusion drafting. Data credibility was assured using method triangulation. The findings revealed that the implementation of learning discipline character had been effectively integrated into classroom activities through habitual compliance with school regulations, maintaining classroom order, completing and submitting assignments on time, wearing the prescribed school uniform, bringing learning materials, praying before lessons, participating in literacy activities, and teachers' role modeling. The main challenges included students' varying levels of self-awareness, individual differences, and limited parental supervision and habituation at home. To address these challenges, teachers implemented continuous disciplinary habituation, role modeling, motivation, supervision, rewards, educational sanctions, and strengthened communication and collaboration with parents. These efforts contributed to enhancing students' awareness of learning discipline and supported the development of character in accordance with the values of Pancasila.